ENHANCING SUSTAINABLE GROWTH THROUGH E-WOM, BRAND IMAGE, PRICE, AND CUSTOMER LOYALTY: EVIDENCE FROM BARENBLISS COSMETICS ON TOKOPEDIA - Irayani; Amrillah Azrin; Mariyam Zanariah; Suharti; Herman Efrizal (Universitas Muhammadiyah Bengkulu, 2026)
The expansion of Indonesia’s digital economy has reshaped marketing practices, particularly in e-commerce, where beauty and personal care products are among the fastest-growing segments. Barenbliss Cosmetics, a Korean beauty brand gaining popularity in Indonesia, benefits from platforms such as Tokopedia to engage young, urban consumers. Prior studies confirm that Electronic Word of Mouth (E-WOM), brand image, and price significantly influence purchase decisions; however, limited research has examined how these variables collectively contribute to customer loyalty and sustainable growth in the cosmetics sector. This study addresses this gap by integrating loyalty and sustainable growth as strategic outcomes, offering a novel perspective that links tactical marketing factors to long-term business performance. The objective of this research is to analyze the effects of E-WOM, brand image, and price on purchase decisions and to investigate how these decisions translate into customer loyalty and sustainable growth. A quantitative approach was employed, with data collected through online questionnaires distributed to Tokopedia consumers who have purchased Barenbliss products. Structural equation modeling (SEM) was applied to test both direct and indirect relationships among variables. The results demonstrate that E-WOM, brand image, and price significantly affect purchase decisions, with brand image emerging as the strongest predictor. Furthermore, customer loyalty is found to mediate the relationship between purchase decisions and sustainable growth. The findings highlight that integrating E-WOM, branding, and pricing strategies is essential not only for influencing short-term consumer behavior but also for ensuring sustainable growth in competitive digital marketplaces.